Pengaruh Free Cash Flow dan Financial Distress Terhadap Manajemen Laba pada Perusahaan Infrastruktur, Utilitas, dan Transportasi Terdaftar Di Bursa Efek Indonesia - Bayu Kurnia; Yati Mulyati (Politeknik Ganesha Medan, 2023)
Financial reports that show company profits and performance are profit and loss reports that are useful for stakeholders and investors to use in considering and estimating an investment or even in making contracts and estimating the viability of a company. Earnings management is one way that can be done. Manager intervention to carry out earnings management by increasing or decreasing profits to achieve a certain profit level to benefit himself or the company. This study aims to determine the effect of free cash flow and financial distress on earnings management. The sample for this study is infrastructure, utilities, and transportation companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The total sample used was 29 companies with 87 observational data obtained. The sampling technique used was the purposive sampling method and testing was carried out with the help of Eviews software. The research results from the data used, for the classic assumption test, have passed the test and have met the established criteria. The results of the F test show that the earnings management variable is influenced simultaneously by the free cash flow and financial distress variables. The results of the t-test show that free cash flow and financial distress have a significant value on earnings management. This study concludes that free cash flow and financial distress have a positive effect on earnings management.